AID–RNA polymerase II transcription-dependent deamination of IgV DNA. Issue 20 (30th September 2019) - Pham, Phuong; Malik, Sohail; Mak, Chiho; Calabrese, Peter C; Roeder, Robert G; Goodman, Myron F
Abstract: Activation-induced deoxycytidine deaminase (AID) initiates somatic hypermutation (SHM) in immunoglobulin variable (IgV) genes to produce high-affinity antibodies. SHM requires IgV transcription by RNA polymerase II (Pol II). A eukaryotic transcription system including AID has not been reported previously. Here, we reconstitute AID-catalyzed deamination during Pol II transcription elongation in conjunction with DSIF transcription factor. C→T mutations occur at similar frequencies on non-transcribed strand (NTS) and transcribed strand (TS) DNA. In contrast, bacteriophage T7 Pol generates NTS mutations predominantly. AID-Pol II mutations are strongly favored in WRC and WGC W overlapping hot motifs (W = A or T, R = A or G) on both DNA strands. Single mutations occur on 70% of transcribed DNA clones. Mutations are correlated over a 15 nt distance in multiply mutated clones, suggesting that deaminations are catalyzed processively within a stalled or backtracked transcription bubble. Site-by-site comparisons for biochemical and human memory B-cell mutational spectra in an IGHV3-23*01 target show strongly favored deaminations occurring in the antigen-binding complementarity determining regions (CDR) compared to the framework regions (FW). By exhibiting consistency with B-cell SHM, our in vitro data suggest that biochemically defined reconstituted Pol II transcription systems can be used to investigate how, when and where AID is targeted.